2018
DOI: 10.18502/kss.v3i3.1888
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Differentiation Strategies to Create Competitive Advantages in Facing Global Markets

Abstract: .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
1
3
0
1
Order By: Relevance
“…This finding shows that the Differentiation Strategy has a significant positive effect on Competitive Advantage so that can interpret by that the higher the level of strategy differentiation implemented by SMEs in Central Java will increasingly have an impact on increasing the excellence of SMEs in competing. This finding supports (Putra et al, 2018) result who found that differentiation strategies can create a competitive advantage. The same resolve is also proven by (Job et al, 2016), which shows in his research that management decision-making on competitive advantage affected by product differentiation.…”
Section: The Effect Of Differentiation Strategy On Competitive Advantagesupporting
confidence: 91%
“…This finding shows that the Differentiation Strategy has a significant positive effect on Competitive Advantage so that can interpret by that the higher the level of strategy differentiation implemented by SMEs in Central Java will increasingly have an impact on increasing the excellence of SMEs in competing. This finding supports (Putra et al, 2018) result who found that differentiation strategies can create a competitive advantage. The same resolve is also proven by (Job et al, 2016), which shows in his research that management decision-making on competitive advantage affected by product differentiation.…”
Section: The Effect Of Differentiation Strategy On Competitive Advantagesupporting
confidence: 91%
“…According to Putra and Suhato (2018), a differentiation strategy may create a competitive advantage by distinguishing a company's business products along many dimensions, and then charging consumers a premium for those goods. Industries that have reached their maturity and are now undergoing a technological change are able to distinguish themselves and become more cost effective.…”
Section: Porters Generic Strategy Modelmentioning
confidence: 99%
“…Day & Wensley (1988) menyatakan ada dua pijakan dalam mencapai keunggulan bersaing, yaitu keunggulan sumber daya dan keunggulan posisi. Sumber-sumber competitive advantage, menurut (Putra et al, 2018) terdiri dari 2 (dua) hal, yaitu: Kepemimpinan biaya dan diferensiasi.…”
Section: Kajian Teoritisunclassified